Three years’ experience of collaborative care pathways on a maxillofacial ward - S. N. Rogers, R. Naylor,* L. Potter, P. Magennis (Blackwell Synergy, 2000)
Collaborative care pathways (CCPs) are a useful way to promote effective clinical practice. They are also known as anticipated recovery pathways, critical pathways, integrated care plans, and care maps. They are intended to optimize patient management through a multidisciplinary approach, and have been reported for various conditions including unstable angina, multiple sclerosis, radical prostatectomy and cystoprostatectomy, and head and neck surgery.